Cat castles : 20 cardboard habitats you can build yourself - Oliver, Carin (Quirk Books, 2016)
"This DYI construction guide includes fun and easy instructions for making cardboard trains, ships, food trucks, rockets and other hideouts. Also included are tips for climbing towers and scratching pads that they'll use to stay sharp. All twenty projects are quick to assemble and require inexpensive and easy-to-find materials. You can customize them to match your cat's wildest desires!" -- partially taken from back cover.